Impact of biofertilisers on iron homeostasis and grain quality in the rice variety Uma under Elevated CO2 - Bhavya, M. S. P.; Manju, R. V.; Viji, M. M.; Roy, S.; Anith, K. N.; Beena, R. (Frontiers in Plant Science, 2023)
The diminishing nutritional quality of rice with increasing concentrations of atmospheric CO2 is currently a major global concern. The present study was designed with the objective of assessing the impact of biofertilisers on grain quality and iron homeostasis in rice under elevated CO2. A completely randomised design with four treatments ([KAU, POP (control), POP+Azolla, POP+PGPR, and POP+AMF]), each replicated three times under ambient and elevated CO2 conditions, was followed. The analysed data revealed that yield, grain quality, and iron uptake and translocation were modified in an unfavourable manner under elevated CO2, which was reflected in the lower quality and iron content of the grains. The response of iron homeostasis in the experimental plants to the application of biofertilisers, especially plant-growth-promoting rhizobacteria (PGPR), under elevated CO2 strongly suggests the possibility of utilising them for designing iron management strategies for achieving higher quality in rice.